2016
DOI: 10.1021/acs.jnatprod.5b01082
|View full text |Cite
|
Sign up to set email alerts
|

IR and Vibrational Circular Dichroism Spectroscopy of Matrine- and Artemisinin-Type Herbal Products: Stereochemical Characterization and Solvent Effects

Abstract: Five Chinese herbal medicines--matrine, oxymatrine, sophoridine, artemisinin, and dihydroartemisinin--were investigated using vibrational circular dichroism (VCD) experiments and density functional theory calculations to extract their stereochemical information. The three matrine-type alkaloids are available from the dry roots of Sophora flavescens and have long been used in various traditional Chinese herbal medicines to combat diseases such as cancer and cardiac arrhythmia. Artemisinin and the related dihydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 45 publications
3
26
0
1
Order By: Relevance
“…The DF and CID spectral methods have been used to aid in the determination of the ACs of several compounds. 22,[32][33][34][35][36][37][38] In addition, the experimental EDF spectra of binaphthol showed differences due to solvent complexation that followed the trend in solvent polarity. 39 In CDSpecTech, the similarity index SI can be calculated for EA, VA, and Raman spectra, and ESI for ECD, VCD, VROA, EDF, VDF, and VROA spectra, using the parametric function equation 19.…”
Section: Technical Detailsmentioning
confidence: 96%
See 1 more Smart Citation
“…The DF and CID spectral methods have been used to aid in the determination of the ACs of several compounds. 22,[32][33][34][35][36][37][38] In addition, the experimental EDF spectra of binaphthol showed differences due to solvent complexation that followed the trend in solvent polarity. 39 In CDSpecTech, the similarity index SI can be calculated for EA, VA, and Raman spectra, and ESI for ECD, VCD, VROA, EDF, VDF, and VROA spectra, using the parametric function equation 19.…”
Section: Technical Detailsmentioning
confidence: 96%
“…The DF and CID spectral methods have been used to aid in the determination of the ACs of several compounds . In addition, the experimental EDF spectra of binaphthol showed differences due to solvent complexation that followed the trend in solvent polarity …”
Section: Program Descriptionmentioning
confidence: 99%
“…The studies showed that effectively accounting for solvent effects is critical to using IR and VCD spectroscopy which provide unique spectroscopic features to differentiate the potential stereoisomers. 134 (Figure 80). A VCD study for the AC determination of 280 provided evidence for the mutually dependent atropisomerism and absoluye configuration.…”
Section: Nitrogenated Compoundsmentioning
confidence: 99%
“…The closeness of DF similarity scores with and without normalization indicates a corresponding closeness among the magnitudes of intensities in the calculated and experimental ratio spectra. This method was applied to a number of small molecules to aid in the determination of their ACs …”
Section: Computationalmentioning
confidence: 99%